1 - The Semantics of Peace and the Role of the Print Media in the 2007-2008 Post-election Violence in Kenya - Benson Oduor Ojwang, (Africa Media Review, 2009)
The controversial elections of December 2007 in Kenya led to killings, mass displacement, injury and widespread socio-economic destabilization. Despite a series of peace rallies and policy guidelines initiated by the government, the resettlement exercise, dubbed ‘operation rudi nyumbani’, was dogged with controversy and discordant voices from politicians, the clergy, residents of ethnic clash-torn areas, as well as the clash victims. Eventually, voluntary reconciliation through reintegration was promoted and the exercise was renamed ‘operation karibu nyumbani’. In this article, the author analyzes the implications of the messages of peace and conflict inherent in the utterances of the key political players as reported by the mainstream newspapers, namely The Daily Nation, The Standard, and their weekend editions Sunday Nation and Sunday Standard. Specifically, the article reviews the language choices that the media used to frame the hopes, fears, expectations and disappointments entailed in the peace messages by setting the agenda through which the public could monitor and evaluate the peace process. It emerges that the Kenyan press oscillated between peace building and peace threatening modes, depending on the prevailing political and public mood.